ПСИХОЛОГІЧНЕ ЗАБЕЗПЕЧЕННЯ СОЦІАЛЬНОЇ ПІДТРИМКИ РОЗВИТКУ ПРОФЕСІОНАЛІЗМУ ФАХІВЦІВ - Бабатенко О. В. (International Journal of Innovative Technologies in Social Science, 2019)
The article analyzes the peculiarities of psychological support of social support for the development of professionalism of specialists in the food industry. Purpose of the article was to determine the peculiarities of the optimization factors of the functional state of food industry professionals in the annual cycle of activity for psychological support of social support for the development of their professionalism. The methodological approach is based on theoretical and methodological provisions on the systemic structure of mental phenomena and the concept of the development of socio-technical systems of activity. Empirical methods of research were used: conversation, observation, questioning, expert evaluation, analysis of the results of activity, psychological experiment (conceptual and formative); psychodiagnostic methods (estimation of solving problems with a computer (by O. Sheviakov), studying memorization of five- digit numbers with subsequent reproduction (by R. Amthauer), concentration of attention on M. Anfimov’s corrective attempt, rings and entangled lines Landolt, distribution of attention on the red-black table K. Platonov, self-assessment of the subjective state by the method of "Feeling-Activity-Mood (FAM)" V. Doskin, psychophysiological (critical frequency of fusion of light flashes), latent periods of simple sensations (LP Methods of arbitrary mental regulation of functional state (autotraining, ideomotor training).